ANALISIS POLA ASUH ANAK PADA KELUARGA BROKEN HOME DI DUSUN TELUK DURIAN KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Luluk Suryaningsih; Nuraini Asriati; Imran Imran (Universitas Tanjungpura, 2020)
AbstractThis recent study was aimed at determining, democratic, and permissive parenting aplied by the broken home families in the Teluk Durian village, Teluk Keramat District Sambas regency. This study was conducted using a qualitative method in the form of descriptive analysis. The data were collected using observation, interviews, and documentation techniques. The finding showed that the parenting applied bay the broken families was divided into three pieces of evidence. In authotarian parenting, Mrs. MR applied the parenting method by restricting her children from making friends by setting rules for their children to interact with other. In democratic parenting, Mrs. WD applied the parenting method by involving them in decision making, giving them the freedom to choose and take action, and approating them with affection. In permissive parenting, Mrs. EY applied the parenting methoad by not caring about children’s friendship, and mot playing enought attention to facilitating children’s needs.Keywords: Broken Home Family, Democratic, Parenting, Permissive